2020
DOI: 10.1038/s41598-020-64360-2
|View full text |Cite
|
Sign up to set email alerts
|

Ecosystem state change in the Arabian Sea fuelled by the recent loss of snow over the Himalayan-Tibetan Plateau region

Abstract: The recent trend of global warming has exerted a disproportionately strong influence on the Eurasian land surface, causing a steady decline in snow cover extent over the Himalayan-tibetan plateau region. Here we show that this loss of snow is undermining winter convective mixing and causing stratification of the upper layer of the Arabian Sea at a much faster rate than predicted by global climate models. over the past four decades, the Arabian Sea has also experienced a profound loss of inorganic nitrate. in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 58 publications
(53 citation statements)
references
References 52 publications
(81 reference statements)
1
43
0
Order By: Relevance
“…Follow-up studies also reported decreasing oxygen concentrations in the western and northern Arabian Sea (Piontkovski and Al-Oufi, 2015;Queste et al, 2018). In the northern Arabian Sea, dissolved oxygen concentrations in the surface mixed layer largely reflect the trend seen in the OMZ, as indicated by a compilation of dissolved oxygen data covering the period from the 1960s to 2010 (Gomes et al, 2014).…”
Section: Recent Trends In the Bay Of Bengal And The Arabian Seamentioning
confidence: 76%
See 4 more Smart Citations
“…Follow-up studies also reported decreasing oxygen concentrations in the western and northern Arabian Sea (Piontkovski and Al-Oufi, 2015;Queste et al, 2018). In the northern Arabian Sea, dissolved oxygen concentrations in the surface mixed layer largely reflect the trend seen in the OMZ, as indicated by a compilation of dissolved oxygen data covering the period from the 1960s to 2010 (Gomes et al, 2014).…”
Section: Recent Trends In the Bay Of Bengal And The Arabian Seamentioning
confidence: 76%
“…We are still uncertain if the recent emergence and persistence of Noctiluca blooms will further intensify the Arabian Sea's OMZ. Satellite-derived Chlorophyll a trends reveal an almost 3-fold increase in phytoplankton biomass, with increases particularly in the northwestern and central Arabian Sea (Goes et al, 2020). With respect to repercussions for the food chain, we are aware that Noctiluca is not a preferred food for most zooplankton but is voraciously grazed upon by gelatinous animals such as salps.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations